피부에 의한 이득 감쇠를 줄이기 위한 FEA 시뮬레이션 기반의 이식형 마이크로폰 설계 및 구현 - 한지훈; 김민우; 김동욱; 성기웅; 조성목; 박일용; 조진호; Han, Ji-Hun; Kim, Min-Woo; Kim, Dong-Wook; Seong, Ki-Woong; Cho, Sung-Mok; et al. (Journal of biomedical engineering research, 2008)
Nowadays, implantable hearing aids have been developed to solve the problems of conventional hearing aids. In case of fully implantable hearing aids, an implantable microphone is necessary to receive sound signal beneath the skin. Normally, an implantable microphone has poor frequency response characteristics in high frequency bands of acoustic signal due to the high frequency attenuation effect of skin after implantation to human body. In this paper, the implantable microphone is designed to reduce the high frequency attenuation effect of a skin by putting its resonance frequency at the attenuated range through a finite element analysis (FEA) simulation. The designed implantable microphone through the simulated results has been fabricated by manufacturing process using bio-compatible materials. By the several in-vitro experiments with pig skin, it has been verified that the designed implantable microphone has a resonance frequency around the starting part of the attenuated range and reduces the attenuation effect.